The Effect Of Development, Safety And Health At Work ( K3) And Competence On Employees Performance At Bengkulu Search And Rescue Bengkulu - Juniarti, Selva; Anggriani, Ida; Effendi, Yanto (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Every organization and company will always strive to improve employees’ performance in the hope that the organization’s goals will be achieved. To achieve these goals, an organization needs leaders or managers who are able to manage the human resources within the organization,namely employees, to improve the efficiency, effectiveness, and productivity of the organization.The purpose of this study is to determine the influence of Occupational Safety and Health (OSH) and Competency on Employee Performance at the Bengkulu Search and Rescue Office. The type of research conducted is quantitative research, with a total sampling method used in this study, meaning that the number of samples taken in this study is 80 people. The data analysis methods used include Validity Testing, Reliability Test, Multiple Linear Regression Analysis, Determination Coefficient, and Hypothesis Testing. The results of this study indicate that Development, Occupational Safety and Health (OSH), and Competency simultaneously (together) significantly influence the performance of employees at the Bengkulu Search and Rescue Office.